Dissecting Aneurysm of the Anterior Temporal Artery: A Rare Case Report and Literature Review - Hou, Kun; Guo, Yunbao; Chen, Hao; Yu, Jinlu (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Dissecting aneurysm located at the trunk of the anterior temporal artery (ATA) is an extremely rare entity of which only a few cases have ever been reported. As a result of the small caliber and supposed non-competency of the ATA, sacrificing of the artery distal to the aneurysm is the mainstay of treatment. In this report, we present a 28-year-old man who was admitted for a ruptured fusiform aneurysm of the left ATA. He underwent resection of the aneurysm combined with superficial temporal artery (STA)-ATA anastomosis. Histopathological study showed that the aneurysm was compliant with an artery dissection. The postoperative process was unremarkable and he was discharged with no neurological deficit. Follow-up angiography showed the anastomosis was patent. ATA is considered a non-competent intracranial artery. Although recently some investigators have conducted cadaveric studies using the ATA as a donor vessel for intracranial-intracranial (IC-IC) bypass, clinical consequences of ATA occlusion have not been reported yet. The supposed safety of ligation of ATA for IC-IC bypass was based on the fact that the anterior temporal lobectomy for temporal lobe epilepsy does not lead to major neurological deficits. This extrapolation could not be arbitrarily used in ATA occlusion for IC-IC bypass. STA-ATA anastomosis is a reasonable option in case of the ATA dissecting aneurysm.
Keywords: anterior temporal artery; superficial temporal artery; intracranial aneurysm; intracranial-intracranial bypass